Diversity and inclusion in Colombian rural education - Buitrago Carreño, Nidia Yiseth (2022)
Education in Colombia or anywhere in the world, has the responsibility of establishing links with society in understanding the current and future needs, problems and challenges to face them effectively, hence the priority of the educational institutions of the century XXI is to promote activities that demonstrate social responsibility such as inclusion as a human right to training from the conception of diversity within the Colombian rural educational context and the organization that frames the characteristics under which educational policies are implemented for attention to the population without distinction compared to the urban sector. Similarly, a reflection is made on the immediate need to carry out a restructuring based on educational policies in order to eliminate the so-called gaps that arise in the educational sector and that allows the educational progress of the rural area always recognizing the efforts s carried out by the state and aiming to face the future challenges to be presented in the educational sector of the country.